Rate of feed passage in Japanese quail - Nóbrega, I. P.T. [UNESP]; Nogueira, H. S. [UNESP]; Lima, M. B. [UNESP]; Sakomura, N. K. [UNESP]; Peruzzi, N. J. [UNESP]; Artoni, S. M.B. [UNESP]; Suzuki, R. M. [UNESP]; Silva, E. P. [UNESP] (Elsevier, 2020)
The rate of passage (ROP) in the gastrointestinal tract (GIT) influences the exposure time of food to the digestion and absorption processes. Consequently, ROP affects the efficiency of nutrient utilization and energy from the diet. This study aimed to determine the physiological parameters that characterize the digestive response, such as first appearance time (FAT), ROP, mean retention time (MRT) and transit time (TT) in adult Japanese quail (Coturnix coturnix japonica), and to evaluate the effects of sex, apparent metabolizable energy corrected for nitrogen balance (AMEn) content in the diet and different types of markers on these parameters. In the first trial, we investigated the effects of sex and AMEn level (high- and low-energy diet) on the FAT parameter. Thirty-two male and 32 female Japanese quail were randomly allocated to 8 battery cages and assigned to 4 treatments in a 2 × 2 factorial design with 4 replicates of 4 birds for each treatment. To determine the FAT, ferric oxide (1%) was added to the diet, and the excreta of the quail was monitored until the first appearance of the marker. The results indicated significant differences (P < 0.05) in the FAT between males (100 min) and females (56 min), regardless of the AMEn content. In the second trial, thirty-two 32-week-old female Japanese quail in the laying phase were assigned to four treatments in a 2 × 2 factorial design, in which the main independent variables were type of marker (Cr or Ti) and AMEn level (high- and low-energy diets). In order to determine ROP (ET1%), MRT and TT (ET100%), the markers (0.5%: Cr2O3 and 0.5%: TiO2) were added to the diets, and the excreta were collected for 750 min. The excretion times for 1% (ET1%), 25% (ET25%), 50% (ET50%), 75% (ET75%) and 100% (ET100%) were estimated using cumulative excretion curves. No effect was detected for the AMEn level (P > 0.05); however, the effect of different marker types was significant (P < 0.05). This difference increased with time and ET100% was estimated to occur at 59 min. The ROP was estimated to be 68 min. The TT was estimated to be 540 min using Cr and 599 min using Ti, with an average MRT value of 0930 h. Taken together, our findings support the hypothesis that Japanese quail digestion through the GIT can be dynamic and differ based on sex or marker type.
Keywords: coturnix quail; markers; mean retention time; metabolizable energy; passage rate